2020
DOI: 10.1111/jfbc.13406
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the DPP‐IV inhibitory activity of a novel octapeptide derived from rapeseed using Caco‐2 cell monolayers and molecular docking analysis

Abstract: The Octapeptide ELHQEEPL, which was identified from the rapeseed protein napin showed prominent Dipeptidyl peptidase-IV (DPP-IV) inhibitory activity. The objective of this study was to investigate the DPP-IV inhibitory activity and transepithelial transport of ELHQEEPL in an approaching intestinal condition using Caco-2 cell monolayers. ELHQEEPL and its degraded fragments EL, HQEEP, and methylated ELHQEEPL were transported across Caco-2 cell monolayers through different pathways. Compared with the nonbiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…They can be attached more firmly to the brush border of human small intestinal epithelial cells to inhibit the effect of the DPP-IV enzyme in the intestinal lumen. As we previously reported, 7 peptide nanogels with RAP1 and RAP2 functional structures could not change the expression of the DPP-IV gene, but decreased the activity of DPP-IV. In addition to degradation during gastrointestinal digestion, the original structure of most of the oligopeptides can also be altered and modified on the intestinal epithelial cells.…”
Section: Resultssupporting
confidence: 54%
“…They can be attached more firmly to the brush border of human small intestinal epithelial cells to inhibit the effect of the DPP-IV enzyme in the intestinal lumen. As we previously reported, 7 peptide nanogels with RAP1 and RAP2 functional structures could not change the expression of the DPP-IV gene, but decreased the activity of DPP-IV. In addition to degradation during gastrointestinal digestion, the original structure of most of the oligopeptides can also be altered and modified on the intestinal epithelial cells.…”
Section: Resultssupporting
confidence: 54%
“…Most studies measure DPP-IV-inhibitory activity using purified and recombinant DDP-IV in vitro. Recently, an in vitro approach involving live intestinal epithelial Caco-2 cells was developed by our team [ 42 ], and has since been used in several studies to assess DPP-IV-inhibitory activity [ 33 , 39 , 42 , 43 , 44 ]. DPP-IV-inhibitory activity has also been measured ex vivo in rat and human plasma [ 13 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neither the individual PIs nor their polymorphisms have been reported in detail. More recently, different oilseed proteins, including from rapeseed, have demonstrated the presence of ACE- and DPP-IV-inhibitory peptides [ 30 , 31 ]. In this study, canola meal from two genetically diverse genotypes was used to discover six protease inhibitors, which were evaluated for their potential antidiabetic and antihypertension potential.…”
Section: Discussionmentioning
confidence: 99%
“…The ACE inhibition IC 50 values of the purified PI preparations of two canola genotypes, purified in this study, were compared with the IC 50 values of compounds from different species. These compounds included in vitro digested dry fruit bodies of Pleurotus ostreatus (IC 50 510 μg/mL) [ 31 ], yeast hydrolyzates (26.13 μg/mL [ 32 ], and chickpea accession BDN-9-3 (IC 50 22430 μg/mL [ 33 ]. Considering these values, canola meal PIs in our studies showed significant potential for ACE inhibition.…”
Section: Discussionmentioning
confidence: 99%